Severely calcified leiomyoma of broad ligament in a postmenopausal woman: Report of a rare case - Subrata Pal; Sajeeb Mondal; Palash Kr Mondal; Gargi Raychaudhuri; Rajashree Pradhan; Suparna Banerjee (Wolters Kluwer Medknow Publications, 2016)
Calcified broad ligament leiomyoma is a rare benign lesion in postmenopausal age group. It causes diagnostic confusion with solid calcified adnexal mass and large bladder calculi at the pelvic region. Clinical and radiological diagnoses were confirmed by histopathology of the hysterectomy specimen. We hereby present a case of heavily calcified broad ligament fibroid in a postmenopausal woman.